(untitled) (Sustainability in Debate, 2024)
In a context where artisanal gold mining is expanding rapidly in West Africa, particularly in Burkina Faso, the debate focuses on the positive and negative impacts of this activity on the environment and human beings. This article analyses the environmental changes, the ecological crisis, and the impacts on human health caused by gold panning in the Bougouriba River catchment area in the southwest of the country. To achieve this, a methodology was adopted that combined the collection, processing, and geospatial analysis of data collected from 100 people chosen at random from the various gold panning sites. The results show that the tools and chemicals used by gold miners cause almost irreversible damage to natural resources and create a risk of disease for the miners themselves, people living in the surrounding villages, and animals. Despite the perceptible harmful effects, gold panning is seen as a ‘necessary evil’ in this basin. The study suggests that the sector needs to be better supervised to reduce the negative impact on the environment and the health of gold miners and neighbouring communities.